Lysine Acetylation/Deacetylation Modification of Immune-Related Molecules in Cancer Immunotherapy - Ding, Peng; Ma, Zhiqiang; Liu, Dong; Pan, Minghong; Li, Huizi; Feng, Yingtong; Zhang, Yimeng; Shao, Changjian; Jiang, Menglong; Lu, Di; Han, Jing; Wang, Jinliang; et al. (Frontiers in Immunology, 2022)
As major post-translational modifications (PTMs), acetylation and deacetylation are significant factors in signal transmission and cellular metabolism, and are modulated by a dynamic process via two pivotal categories of enzymes, histone acetyltransferases (HATs) and histone deacetylases (HDACs). In previous studies, dysregulation of lysine acetylation and deacetylation has been reported to be associated with the genesis and development of malignancy. Scientists have recently explored acetylation/deacetylation patterns and prospective cancer therapy techniques, and the FDA has approved four HDAC inhibitors (HDACi) to be used in clinical treatment. In the present review, the most recent developments in the area of lysine acetylation/deacetylation alteration in cancer immunotherapy were investigated. Firstly, a brief explanation of the acetylation/deacetylation process and relevant indispensable enzymes that participate therein is provided. Subsequently, a multitude of specific immune-related molecules involved in the lysine acetylation/deacetylation process are listed in the context of cancer, in addition to several therapeutic strategies associated with lysine acetylation/deacetylation modification in cancer immunotherapy. Finally, a number of prospective research fields related to cancer immunotherapy concepts are offered with detailed analysis. Overall, the present review may provide a reference for researchers in the relevant field of study, with the aim of being instructive and meaningful to further research as well as the selection of potential targets and effective measures for future cancer immunotherapy strategies.